A novel species in the genus Heveochlorella (Trebouxiophyceae, Chlorophyta) witnesses the evolution from an epiphytic into an endophytic lifestyle in tree-dwelling green algae - Ma, Shuai; Huß, Volker; Tan, Deguan; Sun, Xuepiao; Chen, Jingbo; Xie, Yaoyun; Zhang, Jiaming (European Journal of Phycology, 2013)
Roystonea regia is a popular landscape palm famous for its smoothly sculpted white trunk, but sometimes it is spoiled by epiphytic green algae inhabiting the bark. We identified a trebouxiophycean green alga as the single dominant species growing on the trunk of a royal palm in Hainan, China. Light and transmission electron microscopy showed adult cells to be spherical with a diameter of 6.4-13.7 μm, and to contain a single cup-shaped parietal chloroplast. Each chloroplast contained a pyrenoid of 1.4-2.1 μm in diameter. The pyrenoid was penetrated by radially arranged tubular invaginations surrounded by pyrenoglobuli, which is similar to Heveochlorella hainangensis. Phylogenetic analyses inferred from nuclear-encoded 18S rRNA sequences placed strain ITBB A3-8 in the Watanabea clade (Trebouxiophyceae, Chlorophyta), closely related to H. hainangensis. But strain ITBB A3-8 differs sufficiently from H. hainangensis in significant aspects of ultrastructure, physiology, and nuclear and plastid ribosomal RNA and ITS sequences to be treated as a novel species, H. roystonensis Shuai Ma, V. Huss, Xuepiao Sun & Jiaming Zhang, sp. nov. The growth of the epiphytic H. roystonensis seems to be promoted by air pollution in the city, while the endophytic H. hainangensis requires an organic carbon source for optimal growth. Thus in the genus Heveochlorella both an epiphytic and an endophytic lifestyle of tree-dwelling green algae can be observed. © 2013 British Phycological Society.
Keywords: Epiphytic algae; Heveochlorella hainangensis; Heveochlorella roystonensis sp. nov.; ITS; pyrenoid; SSU rRNA gene phylogeny; Trebouxiophyceae; taxonomy

AtSTP3, a green leaf-specific, low affinity monosaccharide H+ symporter of Arabidopsis thaliana - Büttner, Michael; Truernit, Elisabeth; Scholz-Starke, Joachim; Sontheim, Michaela; Lauterbach, Christian; Huß, Volker; Sauer, Norbert; et al. (Plant Cell and Environment, 2000)
This paper describes the expression analyses of the AtSTP3 gene of Arabidopsis thaliana, the functional characterization of the encoded protein as a new monosaccharide transporter, and introduces the AtSTP gene family. The kinetic properties of the AtSTP3 protein (for sugar transport protein 3) were studied in a hexose transport deficient mutant of Schizosaccharomyces pombe. AtSTP3 represents a new monosaccharide transporter that is composed of 514 amino acids and has a calculated molecular mass of 55.9 kDa. Kinetic analyses in yeast showed that AtSTP3 is a low affinity, energy-dependent H symporter with a K(m) for D-glucose of 2 mM. RNase protection analyses revealed that AtSTP3 is expressed in leaves and floral tissue of Arabidopsis. This expression pattern of the AtSTP3 gene was confirmed in AtSTP3 promoter-β-glucuronidase (GUS) plants showing AtSTP3-driven GUS activity in green leaves, such as cotelydons, rosette and stalk leaves and sepals. Wounding caused an induction of GUS activity in the transgenic plants and an increase of AtSTP3 mRNA levels in Arabidopsis wild-type plants. Polymerase chain reaction analyses with degenerate primers identified additional new AtSTP genes and revealed that AtSTP3 is the member of a large family of at least 14 homologous genes coding for putative monosaccharide-H symporters (AtSTPs).
Keywords: Arabidopsis; AtSTP3; Gene family; Glucose; Monosaccharide transport

Biochemical Taxonomy of Symbiotic Chlorella Strains from Paramecium and Acanthocystis - Kessler, Erich; Huß, Volker (Botanica Acta, 1990)
Biochemical and physiological characters of 5 symbiotic Chlorella strains, 4 of them from Paramecium (Ciliata) and one from Acanthocystis (Rhizopoda, Heliozoa), were studied. Four strains (3 from Paramecium and one from Acanthocystis) belong to the same species. This is characterized by the presence of hydrogenase, no formation of secondary carotenoids, no growth on mannitol, requirements for thiamine and vitamin B, and a G + C content of the DNA of 66.4–68.4 mol%; the limits of growth are at pH 5.5, at up to 1% NaCl, and at 26–30°C. The strains are somewhat heterogeneous in their utilization of inorganic nitrogen sources: only two of them are able to use nitrate, whereas all can grow with nitrite and ammonium. Thus, in two strains the nitrate‐reducing system — in contrast to nitrite reductase — seems to be defective. Another strain, which has been claimed to be from Paramecium, belongs to C. protothecoides. 1990 Deutsche Botanische Gesellschaft/German Botanical Society
Keywords: Biochemical taxonomy; Classification; Chlorella; Vitamin B12 requirement; Inorganic nitrogen sources; Symbiosis; Paramecium; Acanthocystis

Bovine mastitis associated with Prototheca blaschkeae - Marques, Sara; Silva, Eliane; Kraft, Christine; Carvalheira, Júlio; Videira, Arnaldo; Huß, Volker; Thompson, Gertrude (Journal of Clinical Microbiology, 2008)
Bovine mastitis is an important and complex disease responsible for economic losses in the dairy industry. Biotype II strains of the green alga Prototheca zopfii can be involved, most often resulting in chronic mastitis of difficult treatment associated with reduced milk production. This type of infection is rare, but the number of reported cases is increasing worldwide. In order to determine the kind of species involved in mastitis by Prototheca in northwest Portugal, 41 Prototheca isolates were genetically characterized. The algae are part of Prototheca isolates that were collected during a 6-year period, isolated from the milk of 41 dairy cows in a total of 22 herds with a history of increasing somatic cell counts, mild clinical signs of udder infection, and unsuccessful response to the usual therapy. PCR amplification of the 18S ribosomal DNA (rDNA), amplified rDNA restriction analysis, and phylogenetic analyses of the 18S rDNA sequences were performed. Thirty-seven isolates were identified as P. zopfii var. hydrocarbonea and four as Prototheca blaschkeae. These data suggest a high incidence of P. zopfii var. hydrocarbonea mastitis in the region and demonstrate for the first time the involvement of P. blaschkeae with bovine mammary gland infections.

Chlorella: 125 years of the green survivalist - Krienitz, Lothar; Huß, Volker; Bock, Christina (Trends in Plant Science, 2015)
Chlorella, the archetype of unicellular green algae, is a high-performance primary producer in aquatic and terrestrial ecosystems. Under the simple spherical morphology of Chlorella, many other 'green balls' unfolded as independent phylogenetic lineages as a result of convergent evolution. By contrast, green algae with strikingly different phenotypes were unmasked as close relatives of Chlorella by modern molecular techniques. Here, we point to the increasing impact of these diverse protists on ecology, evolution, and biotechnology in the light of integrative taxonomy.
Keywords: Biodiversity; Green algae; Mass cultivation; Microphyte phylogeny; Model organism; Phenotypic adaptation

Chlorella sorokiniana (formerly C. vulgaris) UTEX 2714, a non-thermotolerant microalga useful for biotechnological applications and as a reference strain - Bashan, Yoav; Lopez, Blanca R; Huß, Volker; Amavizca, Edgar; de-Bashan, Luz E (Journal of Applied Phycology, 2016)
Molecular analyses employing sequencing of the complete ribosomal RNA cistron (18S rDNA, ITS1, 5.8S rDNA, ITS2, and 28S rDNA) and transcriptome analysis of the RuBisCO gene (rbcL) were done on Chlorella vulgaris UTEX 2714. The constructed phylogenetic trees showed that C. vulgaris UTEX 2714 is Chlorella sorokiniana. Growth analysis and production of chlorophyll a over a range of increasing cultivation temperatures (27–40 °C) showed that this strain is far less thermotolerant in comparison to a common C. sorokiniana strain. A change in the taxonomic designation of strain UTEX 2714 is proposed.
Keywords: Chlorella; Reference strains; Systematics

Chlorella thermophila (Trebouxiophyceae, Chlorophyta), a novel thermo-tolerant Chlorella species isolated from an occupied rooftop incubator - Ma, Shuai; Han, Bingyin; Huß, Volker; Hu, Xiaowen; Sun, Xuepiao; Zhang, Jiaming (Hydrobiologia, 2015)
Open rooftop incubators may provide a cost-effective way for producing microalgal biomass for biodiesel production without requiring large land areas. While cultivating a Chlorella vulgaris strain with high oil content in a rooftop incubator, we identified an invading thermo-resistant green alga, which replaced the original culture. The isolated strain HTA1-65 had the typical Chlorella morphology with spherical cells and a cup-shaped parietal chloroplast. The protoplast contained a single pyrenoid traversed by a double-layered thylakoid and enveloped by a single starch sheath. The oil content of this strain was only 21.5 %, one third of the original strain. This strain grew at 42 °C, with an optimum of 33 °C. Heat treatment of 45 °C for 3 h per day did not decrease its growth rate, suggesting that it has a high potential in biotechnological applications. Phylogenetic analyses revealed that HTA1-65 belongs to the genus Chlorella, but a specific relationship to any species was not indicated by nuclear and chloroplast small subunit rRNA genes. However, based on at least one compensating base change (CBC) and a few hemi-CBCs in the ITS2 secondary structure of closely related species, we describe strain HTA1-65 as a novel, thermo-tolerant Chlorella species, C. thermophila.
Keywords: Chlorella vulgaris; Chlorella thermophila; Microalgae; Invading species; Rooftop incubator; Phylogenetic analysis

Deoxyribonucleic acid and interspecies relationships of the genus Chlorella (Chlorophyceae) - Huß, Volker; Fischer, Gabriele; Kessler, Erich (Plant Systematics and Evolution, 1989)
Phylogenetic relationships within the genus Chlorella were studied by means of DNA/DNA hybridization under both optimal and relaxed reassociation conditions as well as by determination of the thermal stability of hybrid DNA duplexes. The results indicate a relationship betweenC. fusca var.fusca, C. fusca var.rubescens, C. fusca var.vacuolata, and the genusScenedesmus. In addition, the strains endosymbiotic withParamecium bursaria seem to be related with theC. vulgaris/sorokiniana group. The relations between most other species, however, could not be sufficiently resolved by the above methods. This implies considerable phylogenetic divergency within the genus Chlorell

Hyaloraphidium curvatum is not a green alga but a lower fungus; Amoebidium parasiticum is not a fungus, but a member of the DRIPs - Ustinova, Iana; Krienitz, Lothar; Huß, Volker (Protist, 2000)
The unicellular heterotrophic protist Hyaloraphidium is classified with a family of green algae, the Ankistrodesmaceae. The only species that exists in pure culture and that is available for taxonomic studies is H. curvature. Comparative18S ribosomal RNA sequence analyses showed that H. curvature belongs to the fungi rather than to the algae. Within the fungi, H. curvatrum preferentially clustered with Chytridiomycetes. Unlike Chytridiomycetes, H. curvature propagates by autosporulation, and the presence of flagella has never been reported. Transmission electron microscopy indicated that H. curvature in some respects resembles Chytridiomycetes, but no elements of a flagetlar apparatus were detected. The habitus of H. curvature is unlike that of other fungi except the trichomycete Amoebidium parasiticum. The cell wall sugar composition of H. curvature was unique, but to some extent resembled that of A. parasiticum. However, H. curvature and A. parasiticum are not closely related to each other according to 18S rRNA sequence data. Moreover, A. parasiticum clustered with protistan animals, the Mesomycetozoa (DRIPs). Combined molecular, ultrastructural and chemical data do not allow assignment of H. curvature to any recognized clade of fungi. This suggests that H. curvature may represent an independent evolutionary lineage within the fung

Internal transcribed spacer sequence-based rapid molecular identification of Prototheca zopfii and Prototheca blaschkeae directly from milk of infected cows - Marques, Sara; Huß, Volker; Pfisterer, K.; Grosse, C.; Thompson, G. (Journal of Dairy Science, 2015)
The increasing incidence of rare mastitis-causing pathogens has urged the implementation of fast and efficient diagnostic and control measures. Prototheca algae are known to be associated with diseases in humans and animals. In the latter, the most prevalent form of protothecosis is bovine mastitis with Prototheca zopfii and Prototheca blaschkeae representing the most common pathogenic species. These nonphotosynthetic and colorless green algae are ubiquitous in different environments and are widely resistant against harmful conditions and antimicrobials. Hence, the association of Prototheca with bovine mastitis represents a herd problem, requiring fast and easy identification of the infectious agent. The purpose of this study was to develop a reliable and rapid method, based on the internal transcribed spacer (ITS) sequences of ribosomal DNA, for molecular identification and discrimination between P. zopfii and P. blaschkeae in bovine mastitic milk. The complete ITS sequences of 32 Prototheca isolates showed substantial interspecies but moderate intraspecies variability facilitating the design of species-specific PCR amplification primers. The species-specific PCR was successfully applied to the identification of P. zopfii and P. blaschkeae directly from milk samples. The intraspecific ITS phylogeny was compared for each species with the geographical distribution of the respective Prototheca isolates, but no significant correlation was found.
Keywords: Prototheca spp. bovine mastitis; internal transcribed spacer (ITS); rapid molecular identification; species-specific PCR (ssPCR); geographical distribution

Morphology and phylogenetic position of a trebouxiophycean green alga (Chlorophyta) growing on the rubber tree, Hevea brasiliensis, with the description of a new genus and species - Zhang, Jiaming; Huß, Volker; Sun, Xuepiao; Chang, Kaijun; Pang, Daobiao (European Journal of Phycology, 2008)
A novel unicellular Chlorella-like green alga was isolated from the rubber tree (Hevea brasiliensis). The cultured cells were described by light and electron microscopy. Most adult cells were spherical with a single cup-shaped parietal chloroplast, although a few cells contained 2 to 4 chloroplasts. Chloroplasts contained many small pyrenoids with pyrenoglobuli around the multi-oriented tube-like thylakoids in the pyrenoid matrix. Most sporangia contained 2 or 4 autospores with a spindle-shaped chloroplast. Phylogenetic analyses inferred from both chloroplast-encoded 16S and nuclear-encoded 18S rDNA sequences placed our isolate in the 'Chlorella' luteoviridis clade within the class Trebouxiophyceae. There are two group I introns in the 18S rDNA, structurally similar to 'Chlorella' trebouxioides, which also has two introns at the same positions. The exon sequence revealed highest similarities of 93-95% compared with 'C.' luteoviridis, 'Chlorella' saccharophila, and 'C.' trebouxioides. The chloroplast 16S rDNA has a unique 46-bp insertion in helix P21-1, which can be folded into a double hairpin structure. Blast searches resulted in best hits of 96% similarity to 'C.' luteoviridis (CCAP-211/3), and of 91% to 'C.' saccharophila (SAG 211-1d). Based on morphological features and phylogenetic position, a new genus Heveochlorella gen. nov. with the type species H. hainangensis sp. nov. is proposed. © 2008 British Phycological Society.
Keywords: Chlorella; Chlorophyta; Chloroplast; Double hairpin element; Phylogeny; Pyrenoid; Taxonomy; Trebouxiophyceae

Photosynthetic inorganic carbon acquisition in an acid-tolerant, free-living species of Coccomyxa (Chlorophyta) - Verma, Vidhu; Bhatti, Shabana; Huß, Volker; Colman, Brian (Journal of Phycology, 2009)
The processes of CO acquisition were characterized for the acid-tolerant, free-living chlorophyte alga, CPCC 508. rDNA data indicate an affiliation to the genus Coccomyxa, but distinct from other known members of the genus. The alga grows over a wide range of pH from 3.0 to 9.0. External carbonic anhydrase (CA) was detected in cells grown above pH 5, with the activity increasing marginally from pH 7 to 9, but most of the CA activity was internal. The capacity for HCO uptake of cells treated with the CA inhibitor acetazolamide (AZA), was investigated by comparing the calculated rate of uncatalyzed CO formation with the rate of photosynthesis. Active bicarbonate transport occurred in cells grown in media above pH 7.0. Monitoring CO uptake and O evolution by membrane-inlet mass spectrometry demonstrated that air-grown cells reduced the CO concentration in the medium to an equilibrium concentration of 15 μM, but AZA-treated cells caused a drop in extracellular CO concentration to a compensation concentration of 27 μM at pH 8.0. CO -pulsing experiments with cells in the light indicated that the cells do not actively take up CO . An internal pool of unfixed inorganic carbon was not detected at the CO compensation concentration, probably because of the lack of active CO uptake, but was detectable at times before compensation point was reached. These results indicate that this free-living Coccomyxa possesses a CO - concentrating mechanism (CCM) due to an active bicarbonate-uptake system, unlike the Coccomyxa sp. occurring in symbiotic association with lichens. © 2009 Phycological Society of America.
Keywords: Bicarbonate transport; Carbonic anhydrase; CO2-concentrating mechanism; Dissolved inorganic carbon; Photosynthesis

Phylogenetic characterization and morphological and physiological aspects of a novel acidotolerant and halotolerant microalga Coccomyxa onubensis sp. nov. (Chlorophyta, Trebouxiophyceae) - Fuentes, Juan L; Huß, Volker; Montero, Zaida; Torronteras, Rafael; Cuaresma, Mariá; Garbayo, Inés; Vílchez, Carlos (Journal of Applied Phycology, 2016)
The genus Coccomyxa comprises green microalgae, which can be found worldwide in remarkably versatile aquatic and terrestrial ecosystems including symbiotic associations with a number of different hosts. In this study, we describe a new species, Coccomyxa onubensis, based on 18S and ITS ribosomal DNA (rDNA) sequence data. Coccomyxa onubensis was isolated from acidic water, and its ability to adapt to a wide range of acidic and alkaline pH values and to high salinity was analyzed. The long-termadaptation capacity of the microalga to such extreme conditions was evaluated by performing continuous repeated batches at selected salt concentrations and pH values. Adapted cultures of C. onubensis were found to yield high biomass productivities from pH 2.5 to 9, with maximum yields at acidic pH between 2.5 and 4.5. Moreover, C. onubensis was also found to adapt to salinities as high as 0.5 M NaCl, reaching biomass productivities that were similar to those of control cultures. Ultrastructural analysis by transmission electron microscopy of C. onubensis cells adapted to high salinity showed a robust response to hyperosmotic shock. Thus, C. onubensis was found to be acidotolerant and halotolerant. High biomass productivity over a wide range of pH and salinities denotes C. onubensis as an interesting candidate for various biotechnological applications including outdoor biomass production.
Keywords: Coccomyxa; Green algae; Phylogeny; Acidotolerance; Halotolerance; Biotechnology